Gramscianism in Syed Husin Ali's neo-feudalism: a postcolonial appraisal - Zamri, Zahid; Sidhu, Jatswan Singh (Malaysian Social Science Association (MSSA) and Institute of Malaysian and International Studies (IKMAS,UKM), 2021)
Since the end of the World War II, subjects within the former British colonies had been propagated with the “vulgarity” of communism in order to impede the spread of left-leaning ideologies as a means to maintain the domination the former colonial masters over their colonised territories. This happened especially in the British ex-colonies in Southeast Asia including Malaysia. The case of Syed Husin Ali is such an example who has been smeared with such propaganda. As an academic in a long-established Malaysia’s post-independence regime and also a party leader, Syed Husin was detained without trial under the Internal Security Act (ISA) for nearly seven years on the alleged charge of spreading “subversive communism” to university students. Using postcolonial lens, this article examines Syed Husin’s thoughts on neo-feudalism − one of the main ideas that he had frequently highlighted in his works and party-speeches. This article shows that Syed Husin’s ideas on neo-feudalism have ideological homologies with Gramscian concepts, thus further rejecting the claims that he is an orthodox Marxist or one simply leaning towards Weberian perspectives of stratification.